Pelatihan Mekanisme Desalinasi dengan Menggunakan Metode Konvensional dan Metode Distilasi di Pokdarwis Lantebung Kota Makassar - Sri Wulandari; Darmawati Darmawati; Mesalina Tri Hidayani; Suprianto Suprianto (CV. Ulil Albab Corp, 2024)
Desalination is the process of removing salt from seawater or brackish water so that it can become fresh water. The term has long been coined but not many people have practised it, including members of the Lantebung Tourism Awareness Group (Pokdarwis). The community of Lantebung has reportedly been experiencing clean water shortages for the past five years, while the coastal sea water of Lantebung stretches for 9.69 km. This activity aims to provide knowledge to Pokdarwis Lantebung regarding desalination, and provide training to Pokdarwis Lantebung regarding desalination mechanisms, both conventionally using sunlight through the evaporation process, as well as using water distiller purification. This community service was carried out on 26 October 2024 at the house of the Chairperson of Pokdarwis Lantebung in Lantebung, Bira Village, Tamalanrea Sub-district, Makassar City with a training theme with four main stages, namely preparation and planning, socialisation, training and application, as well as assistance and evaluation. The conclusion of the service showed that there was an increase in the knowledge of Pokdarwis Lantebung members related to desalination based on the comparison of the pre-test and post-test that had been given, where between the pre-test and post-test six presenters presented six different materials according to their fields of expertise. In addition, the training on desalination mechanisms using conventional methods and distillation methods using water distiller purification went smoothly and was fully supported through the enthusiasm of the participants in the entire series of activities.